Anti-inflammatory effect of a curcumin-aspirin derivative on Ureaplasma-induced cytokine expressions in neonatal monocytes - Jiang, Yan; Heqin, Li; Xiangping, Yi; Hui, Ye (Cellular and Molecular Biology, 2018)
One of the major contributors to death in infants is infant respiratory distress syndrome (IRDS). The transition from early acute inflammation to fibrotic hyperplasia is important in the development of IRDS. However, there are no available and effective remedies for suppression of the early inflammation. In this study, the effect of a curcumin-aspirin (C-A) derivative on the expressions of interleukin (IL)-10, IL-8, tumor necrosis factor (TNF)-Î±, IL-1Î², toll-like receptor (TLR)4 and TLR2 was investigated in neonatal monocytes exposed to Ureaplasma parvum. The techniques used were qPCR and flow cytometry. The results revealed that C-A exerted anti-inflammatory effects on stimulated monocytes and significantly suppressed Ureaplasma-stimulated changes in IL-8, TNF-Î± and IL-1Î² levels. It did not produce any inflammation or apoptosis in the neonatal cells. Moreover, C-A enhanced IL-10 expression and suppressed the expressions of TLR2 and TLR4, indicating that curcumin-aspirin derivative might hold therapeutic potential for early IRDS.